Analysis of the Influence of Fear of Missing Out (FOMO) and the Role of Influencers on Tourism Destination Selection - Setiawan, Rahyuniati; Garliani, Gita; Rahmawati, Dina (Fakultas Ekonomi Universitas Garut, 2024)
The aim of this research is to gain a deeper understanding of the factors that motivate Garut people in choosing tourist destinations by taking into account the influence of Fear of Missing Out (FOMO) and the role of TikTok influencers. The analytical method used in this research is SEM (Structural Equation Modeling). In this research, non-probability sampling techniques were used with a purposive sampling method to determine the research sample. The conclusion obtained from this research is that the fear of missing out can influence the choice of tourist destination through its impact on motivation, emotional responses and behavior. And influencers, especially through social media, film and television, play an important role in shaping tourist perceptions and influencing a person's choice of tourist destination.